Transduction of c-src coding and intron sequences by a transformation-defective deletion mutant of Rous sarcoma virus. - Soong, M M (1986)
The mechanism of cellular src (c-src) transduction by a transformation-defective deletion mutant, td109, of Rous sarcoma virus was studied by sequence analysis of the recombinational junctions in three td109-derived recovered sarcoma viruses (rASVs). Our results show that two rASVs have been generated by recombination between td109 and c-src at the region between exons 1 and 2 defined previously. Significant homology between td109 and c-src sequences was present at the sites of recombination. The viral and c-src sequence junction of the third rASV was formed by splicing a cryptic donor site at the 5' region of env of td109 to exon 1 of c-src. Various lengths of c-src internal intron 1 sequences were incorporated into all three rASV genomes, which resulted from activation of potential splice donor and acceptor sites. The incorporated intron 1 sequences were absent in the c-src mRNA, excluding its being the precursor for recombination with td109 and implying that initial recombinations most likely took place at the DNA level. A potential splice acceptor site within the incorporated intron 1 sequences in two rASVs was activated and was used for the src mRNA synthesis in infected cells. The normal env mRNA splice acceptor site was used for src mRNA synthesis for the third rASV.